2008
DOI: 10.1029/2008ja013366
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐low‐frequency waves and associated wave vectors observed in the plasma sheet boundary layer by Cluster

Abstract: [1] Waves in the Pc1-Pc2 frequency range (0.1-5 Hz) are studied using Cluster magnetic field data. In the plasma sheet boundary layer, Cluster observed harmonically related waves with the fundamental near the local proton cyclotron frequency (W p ). These waves had components both parallel and perpendicular to the local magnetic field (B 0 ). Application of the wave telescope yielded the full wave vector (k) of the waves and showed that they propagated nearly perpendicular to B 0 . Associated with the waves we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 38 publications
4
27
0
Order By: Relevance
“…Wave activity has often been suggested as the agent responsible for part or all of this transition [e.g., Gary and Winske, 1990] (and others reviewed by Broughton et al [2008]), and the harmonic waves reported here show a very close observational link to the PSBL, and, in particular, to its ring-shaped particle distributions. These waves may thus play an important role in energizing the plasma sheet.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Wave activity has often been suggested as the agent responsible for part or all of this transition [e.g., Gary and Winske, 1990] (and others reviewed by Broughton et al [2008]), and the harmonic waves reported here show a very close observational link to the PSBL, and, in particular, to its ring-shaped particle distributions. These waves may thus play an important role in energizing the plasma sheet.…”
Section: Discussionsupporting
confidence: 64%
“…Broughton et al [2008] reviewed many earlier studies investigating possible instabilities that might drive them, and suggested that the two most likely sources of these multiple-harmonic waves were (1) inverse Landau resonance with an accelerated electron beam as described by Chaston et al [2002], or (2) the electromagnetic ion/ion instability caused by coupling between a slow wave on the ion beam and the background ions, as described by Winske and Omidi [1992].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations